2021
DOI: 10.1101/2021.01.25.428136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mRNA-1273 efficacy in a severe COVID-19 model: attenuated activation of pulmonary immune cells after challenge

Abstract: The mRNA-1273 vaccine was recently determined to be effective against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from interim Phase 3 results. Human studies, however, cannot provide the controlled response to infection and complex immunological insight that are only possible with preclinical studies. Hamsters are the only model that reliably exhibit more severe SARS-CoV-2 disease similar to hospitalized patients, making them pertinent for vaccine evaluation. We demonstrate that prime or prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…Proinflammatory pathways of IL6, IL1, and TNFA, signatures of macrophages, neutrophils, and the complement and coagulation cascades were reduced in Ad26.COV2.S immunized hamsters and macaques compared with sham unvaccinated animals. Similar to our findings, single-cell transcriptomic profiling in hamsters showed proinflammatory pathways, neutrophils and macrophages signatures were enriched in the lungs of sham infected hamsters compared with hamsters that received the mRNA-1273 vaccine [ 32 ], suggesting that both mRNA-1273 and Ad26.COV2.S averted proinflammatory pathways induced by SARS-CoV-2 challenge. Similarly, Doremalen and colleagues [ 33 ] showed that ChAdOx1 nCoV-19 did not increase serum level of proinflammatory cytokines such as TNF-α, IL-2, IL-4, IL-5 and IL-6 and prevented damage of the lungs in macaques challenged with SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 87%
“…Proinflammatory pathways of IL6, IL1, and TNFA, signatures of macrophages, neutrophils, and the complement and coagulation cascades were reduced in Ad26.COV2.S immunized hamsters and macaques compared with sham unvaccinated animals. Similar to our findings, single-cell transcriptomic profiling in hamsters showed proinflammatory pathways, neutrophils and macrophages signatures were enriched in the lungs of sham infected hamsters compared with hamsters that received the mRNA-1273 vaccine [ 32 ], suggesting that both mRNA-1273 and Ad26.COV2.S averted proinflammatory pathways induced by SARS-CoV-2 challenge. Similarly, Doremalen and colleagues [ 33 ] showed that ChAdOx1 nCoV-19 did not increase serum level of proinflammatory cytokines such as TNF-α, IL-2, IL-4, IL-5 and IL-6 and prevented damage of the lungs in macaques challenged with SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, rhesus macaques vaccinated with Ad26 had significantly reduced upper and lower respiratory titers although across vaccine candidates evaluated, more robust protection was observed in the BAL than nasal swabs ( Mercado et al, 2020 ). Of the vaccine efficacy studies have been conducted in hamsters ( Brocato et al, 2021 ; Fischer et al, 2021 ; Hörner et al, 2020 ; Meyer et al, 2021 ; Mohandas et al, 2021 ; Rauch et al, 2021 ; van der Lubbe et al, 2021 ; Wu et al, 2021 ; Yinda et al, 2021 ; Zhang et al, 2021 ), those that evaluated infectious virus in upper airways, including unmodified mRNA ( Rauch et al, 2021 ), measles-vectored ( Hörner et al, 2020 ), and Ad26-vectored ( van der Lubbe et al, 2021 ) approaches, were unable to induce sterilizing protection in the upper airway of a majority of animals while an inactivated rabies virus-vectored approach was able to do so ( Kurup et al, 2021 ). An important consideration of the above referenced studies is that these were within the context of A.1 vaccination and matched A.1 viral challenge; therefore, continued evaluation of deployed vaccines and those under development against emergent VoCs is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The Syrian hamster SARS-CoV-2 infection model is characterized by natural susceptibility to SARS-CoV-2 and development of a robust upper and lower respiratory tract infection 6 . The hamster model has been successfully used for the preclinical development of several vaccines including the Ad26 and mRNA-1273 vaccines by Janssen 7 and Moderna 8 , respectively. Several groups have reported the effect of spike protein substitutions observed in B.1.1.7 and B.1.351 VOCs on the virus neutralizing capacity of serum obtained from vaccinated or convalescent individuals.…”
Section: Mainmentioning
confidence: 99%